Precision medicine and Friedreich ataxia: promoting equity, beneficence, and informed consent for novel gene therapies - Faith A. A. Kwa; Evie Kendal (International Journal for Equity in Health)
Abstract Friedreich Ataxia (FA) is an incurable neurodegenerative disease with systemic consequences affecting vital organs including those of the central and peripheral nervous systems. This article will use FA as an example to explore some of the practical and ethical issues emerging in precision medicine for rare diseases. It will first describe the existing management strategies available for FA patients, before considering the potential impact of gene therapy trials on the prevention and treatment of disease symptoms. Finally, ethical considerations will be discussed, including equity of access and managing resource allocation dilemmas; balancing benefits, burdens and harms; and gaining informed consent for novel treatments.